2007
DOI: 10.1182/blood-2006-10-054973
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of IL-21–mediated proliferation

Abstract: Interleukin-21 (IL-21 IntroductionIL-21 is produced mainly by activated CD4 ϩ T cells and regulates functions of T, B, natural killer (NK), and myeloid cells. IL-21 signaling requires the heterodimerization of the IL-21R and ␥ c cytoplasmic domains. 1,2 ␥ c is also shared by the receptors for IL-2, IL-4, IL-7, IL-9, and IL-15, and is mutated in patients with X-linked severe combined immunodeficiency (XSCID), a disease in which T and NK cells are absent and B cells are not functional. 3 Defective IL-21 signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
261
2
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 265 publications
(282 citation statements)
references
References 55 publications
17
261
2
2
Order By: Relevance
“…IL-21 is thus distinct from IL-2, IL-7, and IL-15, which mainly activate STAT-5 (19). Although, the activation of STAT-1 by IL-21 was not previously detected by Brenne et al (8) in myeloma cells, we found it in the current study that is in agreement with numerous other studies on other cell types (12,20). Kinetics study indicates that Stat-1 activation is more transient than Stat-3 activation showing that STAT-3 might play a greater role in IL-21 induced clonogenicity.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…IL-21 is thus distinct from IL-2, IL-7, and IL-15, which mainly activate STAT-5 (19). Although, the activation of STAT-1 by IL-21 was not previously detected by Brenne et al (8) in myeloma cells, we found it in the current study that is in agreement with numerous other studies on other cell types (12,20). Kinetics study indicates that Stat-1 activation is more transient than Stat-3 activation showing that STAT-3 might play a greater role in IL-21 induced clonogenicity.…”
Section: Discussionsupporting
confidence: 83%
“…This result is consistent with the notion that STAT-1 is a negative regulator of cell growth and survival (21) whereas Stat-3 is a positive regulator of survival and promotes oncogenesis (22). In addition to the JAK/STAT pathway, certain ␥c dependent cytokines can activate MAPK and PI3K/Akt pathways (20). In myeloma cells, we found that IL-21 triggers a rapid Erk 1/2 phosphorylation, a pathway known to contribute to proliferation.…”
Section: Discussionsupporting
confidence: 79%
“…A similar differential pattern of STAT molecule activation by IL-15 and IL-21 was observed in murine CD8 ϩ T cells. 43 However, an important difference between CD8 ϩ T cells and CLL cells is that IL-21 cooperates with IL-15 in inducing CD8 ϩ T-cell proliferation and function, 55 while IL-21 counteracts the antiapoptotic and proliferative effects of IL-15 in human CLL cells. The predominant activation of STAT3 by IL-21 may depend on the presence of an YXXQ STAT3 consensus binding motif 56 in the IL-21R intracytoplasmic domain, whereas STAT1 phosphorylation could be related to the activation of JAK1.…”
Section: Discussionmentioning
confidence: 99%
“…Our present findings only partially differ from the recent observation that IL-21 induces signaling via the Shc molecule in mouse CD8 ϩ T cells, albeit less efficiently than IL-15. 43 The different ability of IL-15 and IL-21 to activate ERK1/2 phosphorylation could explain both the antiapoptotic and the mitogenic activity of IL-15. Indeed, the MEK inhibitor UO126 blocked both the mitogenic and antiapoptotic activity of IL-15 on CLL cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation